Environmental Quality Assessment of Bien Hoa City, Dong Nai Province by UEQ Index - Nguyen, Thi Tinh Au (Journal of Technical Education Science, 2023)
Poor surface water quality, air pollution, solid waste collection, domestic water supply, and many more environmental issues are plaguing urban areas due to policies encouraging fast urbanization but failing to synchronize infrastructure. This has heightened the importance of urban environmental management. This project conducts an urban environmental quality assessment (UEQ) in Bien Hoa City, the political, economic, cultural, and social heart of Dong Nai province, and a Grade I urban region in the Southern Key Economic Region. The PRS framework serves as the basis for the process used to establish environmental indicators, with the indicator’s parameters and weight being established using a Delphi process. Seven component indicators and twenty-sixth indicators were calculated as a result. With a score of 44.4 on the UEQI, Bien Hoa City is deemed to have a merely "average" urban environment. The indicators for the individual parts are middling at best. Although Bien Hoa City’s urban environmental quality index is subpar, timely improvements have steadily raised it and each of its indicators and will continue to do so.